Firing wear at use of synthetic oils - Кудрін, А.П.; Маленко, В.І. (Proceedings of National Aviation University (archive), 2004)
The features of the mechanism of greasing action for synthetic oils are considered. The results of researches of starting wear processes of contact surfaces in environment of synthetic oils are given. The comparison of starting wear processes is executed at use of synthetic and mineral oils. Are determined criterion estimations of interrelation of quality of greasing process with triboproperties of tribojunctions.